Dual defense: melatonin simultaneously mitigates cadmium toxicity and southern blight in peanut - Sang, Suling; Tian, Shan; Xu, Wen; Shi, Haojie; Deng, Benliang (Frontiers in Plant Science, 2025)
Peanut (Arachis hypogaea L.), a vital oilseed crop, faces severe yield losses from Southern blight (Sclerotium rolfsii) and cadmium (Cd) contamination in agricultural soils. While crops often endure combined abiotic-biotic stresses in nature, synergistic solutions remain limited. Here, we investigated melatonin’s dual role in enhancing Cd detoxification and disease resistance using physiological assays and LC-MS metabolomics in peanut seedlings. Under combined stress (1 mM CdCl2 + S. rolfsii), melatonin treatment reduced disease incidence by 75% and Cd accumulation by 57% (roots) and 37% (shoots). Mechanistically, melatonin upregulated jasmonic acid biosynthesis genes (AhLOX7, AhOPR3) and ABC transporter genes (ABCC3, ABCC4), potentiated the antioxidant system (SOD: +135%; CAT: +128%), and significantly mitigated Cd-induced oxidative damage. Metabolomics revealed preferential resource allocation to defense metabolites, with marked accumulation of key antioxidants (e.g., uric acid) and defense phytohormones (e.g., salicylic acid, jasmonic acid) over primary metabolism. These findings demonstrate melatonin’s capacity to rewire stress-responsive metabolism, balancing Cd detoxification and pathogen defense without growth penalties. Our study provides the first evidence that melatonin confers dual resistance by reprogramming defense-related pathways, offering a scalable strategy for cultivating stress-resilient peanuts in contaminated agroecosystems, with implications for similar oilseed crops.